2015
DOI: 10.1109/lgrs.2015.2414897
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling GOES Land Surface Temperature for Assessing Heat Wave Health Risks

Abstract: Recent years have witnessed an emerging concern of the health impact of heat waves. A common approach to investigate heat waves is to resort to the geostationary thermal infrared imagery, such as those from the Geostationary Operational Environmental Satellite (GOES) and Meteosat Second Generation. However, coarse spatial resolutions of geostationary images cannot meet the need of assessing and monitoring heat waves in complex urban settings. To address the spatial and temporal variability of heat waves in urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Likewise, various regression tools have been employed to establish the relationships between regression kernels and LST. Several statistical models have been widely applied, including multivariate linear regression [34,58], piecewise linear regression [62], principal component regression [52,53], and geographically weighted regression [11]. These tools can achieve satisfactory enhancement results for rather homogeneous areas [19] and provide rapid enhancement due to their relatively low computational complexity [63].…”
Section: Regression Kernels and Toolsmentioning
confidence: 99%
“…Likewise, various regression tools have been employed to establish the relationships between regression kernels and LST. Several statistical models have been widely applied, including multivariate linear regression [34,58], piecewise linear regression [62], principal component regression [52,53], and geographically weighted regression [11]. These tools can achieve satisfactory enhancement results for rather homogeneous areas [19] and provide rapid enhancement due to their relatively low computational complexity [63].…”
Section: Regression Kernels and Toolsmentioning
confidence: 99%
“…Studies have suggested that DTCs are directly related to plant water stress and soil drought (Fensholt et al, 2011;Stisen et al, 2008;Hernandez-Barrera et al, 2017); thus, such a relationship has been utilized for mapping evapotranspiration (Anderson et al, 2011) and soil moisture (Piles et al, 2016). In addition, it helps improve meteorological forecasting through data assimilation (Orth et al, 2017), extreme heat wave assessments (Hrisko et al, 2020;Jiang et al, 2015), crop yield estimations (Anderson et al, 2016), LST spatiotemporal-scale conversions (Hu et al, 2020), orbit drift corrections of Advanced Very High Resolution Radiometer (AVHRR) LST data (Jin and Treadon, 2003), and vegetation phenology analyses (Piao et al, 2015). Considering the great potential of DTCs in scientific applications and the high temporal variability in LSTs, accurate diurnal LST datasets are crucial for the research community and public (Chang et al, 2021;Hrisko et al, 2020;Pinker et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Land surface temperature (LST, T s ) and air temperature (T a ) are key parameters for analyzing the thermal environment. Both the urban heat island (UHI) and heat waves have relationships with thermal environmental characteristics, yet the study of the UHI focuses more on the long-term climate, and heat waves are more concerned with short-term meteorological conditions (Jiang et al, 2015). To date, most studies have focused on deriving the LST from thermal infrared and microwave channels as well as its application to the urban heat island (Weng et al, 2005;Sobrino et al, 2012;Tomlinson et al, 2012;Ngie et al, 2014;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although the Advanced Very High Resolution Radiometer (AVHRR) produces 1-2 images per day for the same area and the Moderate-resolution Imaging Spectroradiometer (MODIS) onboard the Terra and Aqua satellites can acquire up to four images in middle and high-latitude areas, these techniques cannot capture the continuous temporal variance of heat waves in a day. The geostationary satellite imager has a much higher frequency of observation, but it cannot meet the need for assessing and monitoring detailed heat waves in complex settings (Jiang et al, 2015). Therefore, a common solution for characterizing heat wave characteristics is to downscale images to obtain a higher spatial resolution while maintaining the temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation